Markets on the margins : mineworkers, job creation & enterprise development - Philip, Kate (Writer on economic development projects) (James Currey, 2018)
"Examines more than a decade of enterprise development strategies in marginal economic contexts in South Africa's mining communities and shows how this might impact on development strategies."--Publisher's description